2005
DOI: 10.1093/tropej/fmh103
|View full text |Cite
|
Sign up to set email alerts
|

Late Presentation of Tracheobronchial Foreign Body Aspiration in Children

Abstract: The diagnosis of tracheobronchial foreign body (FB) aspiration in children is often delayed or overlooked. The aim of this study is to examine the causes of delay (>1 month) in the diagnosis and to study the complications of late presentation and their management. During the period between July 1993 and August 2002, 128 patients with suspected FB aspiration were admitted to KKUH, Riyadh, Saudi Arabia. Twenty-eight patients out of 128 patients presented late (>1 month). The medical records of those 28 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 0 publications
2
36
0
2
Order By: Relevance
“…The frequency of radiopaque foreign bodies is in agreement with data in the literature, (1,10,22,23) as does the frequency of normal X-ray results, (23,24) showing that X-rays might not be as conclusive regarding the diagnosis. (25) The predominant location of the foreign body was the right lung, as has been observed in other studies.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The frequency of radiopaque foreign bodies is in agreement with data in the literature, (1,10,22,23) as does the frequency of normal X-ray results, (23,24) showing that X-rays might not be as conclusive regarding the diagnosis. (25) The predominant location of the foreign body was the right lung, as has been observed in other studies.…”
Section: Resultssupporting
confidence: 87%
“…The localized inflammatory process can be explained by the fact that the predominant locations of the foreign bodies were the lung and trachea, whereas the laryngeal edema could be explained by the aspiration of fish bones and their location in the larynx. (1,2,10,21) In most cases, there were no complications related to the endoscopic examination. (1,22) The presence of mild glottic edema and small hemorrhages during the examination, typically excluded by other authors, (23,28) were included here.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[20,21] Bonchial changes (thickening of bronchial wall, cartilage damage and fi brosis) appear when the retention of FBs is longer than 30 days. [22] We found previously the relationship between retention of FB and airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in 21.8% of the cases diagnosis was delayed longer than 30 days. [3] Diagnosis requires advanced methods in cases of aspiration disregard or unawareness. [4,5] Especially in the elderly and with delayed diagnosis of aspiration, severe complications such as shortness of breath, chronic cough, pneumonia, atelectasis can follow.…”
Section: Discussionmentioning
confidence: 99%